If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) = x + 27 Reorder the terms: 3(5 + x) = x + 27 (5 * 3 + x * 3) = x + 27 (15 + 3x) = x + 27 Reorder the terms: 15 + 3x = 27 + x Solving 15 + 3x = 27 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 15 + 3x + -1x = 27 + x + -1x Combine like terms: 3x + -1x = 2x 15 + 2x = 27 + x + -1x Combine like terms: x + -1x = 0 15 + 2x = 27 + 0 15 + 2x = 27 Add '-15' to each side of the equation. 15 + -15 + 2x = 27 + -15 Combine like terms: 15 + -15 = 0 0 + 2x = 27 + -15 2x = 27 + -15 Combine like terms: 27 + -15 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 27=15+y | | 1/2x+3/4=5/12 | | 2g-13=15 | | Z+68=77 | | S+11=50 | | 20-9x=x+10x | | G+28=44 | | 4(2x-3)-6x=20 | | 5=x+37 | | 1/26+6/13 | | 12+m=28 | | -2p+1/5p+6=7 | | 9k+4.3=k+5 | | 10=r+3 | | 10=r+13 | | 3(x-7)=5(x+6) | | 72=N+51 | | (d-2)/4=2d+3 | | B+17=42 | | 25=-5(-7)-5y | | 45+2y=-7y | | C+38=54 | | 2a+77=2a-1 | | 2(x-4)=13 | | 11(86-7y/11)+y=86 | | 5(x-9)+3=5x-43 | | 11(86-7y/11) | | 7k-(k+5)=6k-7 | | 0.16(y-7)+0.06y=0.02y-2.5 | | 2a+b=x | | 31=p+13 | | 3(-7)10y=30 |